Behavioural effects of phenobarbitone and phenytoin in small children. Issue 11 (November 1981) - Bacon, C J; Cranage, J D; Hierons, A M; Rawlins, M D; Webb, J K
Abstract : Mothers of 56 children under 2 years old taking phenobarbitone and mothers of 55 children taking phenytoin recorded on questionnaires changes they had noted in the children's behaviour 3 and 9 weeks after starting the drug. Severe behavioural disturbance was noted by many, but the pattern and incidence was similar to that recorded by the mothers of 50 children starting a placebo, and we attribute it to the effect of a recent hospital admission. There was a small improvement in the behaviour of 20% of children who had been taking phenobarbitone for a year when they stopped it, but in this age group the disturbance caused by phenobarbitone did not appear to have been great.